Influence mechanism of welding time and energy director to the thermoplastic composite joints by ultrasonic welding. (January 2019) - Tao, Wang; Su, Xuan; Wang, Haohan; Zhang, Zenghuan; Li, Hao; Chen, Jie
Abstract: CF/PEEK composites were welded assisted by ultrasonic. The influence of vibration time and using of energy director (ED) to the joints were investigated in details. The joints had defect of incomplete fusion at the interface under short welding time without ED, and defects of cracks and voids appeared at the interface of carbon fiber and PEEK resin, which attributed to too much heat accumulation at the heat affected zone (HAZ). By using flat ED, joint with sound bonding was realized under vibration time of 0.9 s. The lap shear strength of joint can reach 28 MPa, and the joint fractured at the HAZ. The real-time temperature at interfaces were monitored. It is found that the heating rate can be accelerated by using flat ED, and the peak temperature was lowered. At last, the influence mechanism of processing parameter to the joint were discussed in details.